1982
DOI: 10.1523/jneurosci.02-11-01651.1982
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes in deafferented central neurons of an insect, Acheta domesticus. I. Effects upon amino acid uptake and incorporation

Abstract: Chronic cercal deafferentation of the terminal ganglion in developing crickets (Acheta domesticus), which is known to suppress normal development of giant interneuron dendritic arborizations is shown here to reduce [3H]leucine uptake and incorporation into ganglion proteins. Short term deafferentation of adult crickets, in contrast, does not depress amino acid uptake and incorporation significantly. Following unilateral long term deafferentation of the terminal ganglion, a comparison was made of the [3H]leucin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…These cells respond to removal of cereal sensory axon terminals during postembryonic development with substantial retardation ofgrowth of dendritic processes and spines and by alterations in physiological response properties. We have shown that these changes coincide with a marked decrease in protein synthetic capacity within the dendrites and somata of deafferented giant interneurons (Meyer and Edwards, 1982). These findings suggested that the presence of afferent terminals might serve to regulate transneuronally the level of protein metabolism within giant interneurons during postembryonic development.…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…These cells respond to removal of cereal sensory axon terminals during postembryonic development with substantial retardation ofgrowth of dendritic processes and spines and by alterations in physiological response properties. We have shown that these changes coincide with a marked decrease in protein synthetic capacity within the dendrites and somata of deafferented giant interneurons (Meyer and Edwards, 1982). These findings suggested that the presence of afferent terminals might serve to regulate transneuronally the level of protein metabolism within giant interneurons during postembryonic development.…”
mentioning
confidence: 63%
“…Procedures for rearing, maintaining, and deafferentating crickets by cercectomy are described in detail elsewhere (Edwards and Pallor, 1974;Meyer and Edwards, 1982;Palka and Edwards, 1974). Briefly, deafferentation was achieved by removing one or both of the paired cereal appendages ( Fig.…”
Section: Deafferentationmentioning
confidence: 99%
See 3 more Smart Citations